Pengaruh Kompensasi, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Kubota Indonesia - Syahputra, Ilham Dwi; Yunianto, Askar (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine and analyze the influence of compensation, work motivation, and work discipline on the performance of employees at PT. Kubota Indonesia. The respondents of this study are all employees of PT. Kubota Indonesia, totaling 95 people. The sampling technique used is saturated sampling (census) and the data were analyzed using multiple linear regression. Data were collected through the distribution of questionnaires to the employees of PT. Kubota Indonesia and analyzed using SPSS. The results of the study indicate that compensation has a positive effect on employee performance, work motivation has a positive and significant effect on employee performance, and work discipline also has a positive and significant effect on employee performance.